Seedbed Preparation and Planting Depth Affect Switchgrass Establishment and Yield. Issue 1 (15th September 2016) - Butler, Twain J.; Stein, Jimmy D.; Pittman, Jeremy J.; Interrante, Sindy M.
Abstract : Core Ideas: Switchgrass has potential for renewable biofuel production. It is productive under nutrient‐ or water‐limited environments. It can be no‐till planted on lands that are susceptible to erosion. Switchgrass ( Panicum virgatum L.) is a native, long‐lived, warm‐season perennial grass that is well adapted, has potential for biofuel production, and can improve soil chemical and physical properties. It can be difficult to establish, but it can be productive in marginally productive or difficult to cultivate lands, and its root system can aid in soil conservation. The objectives of this 2‐year field experiment were to determine the effects of seedbed preparation (burning, mowing, or tilling) and planting depth (0.25, 0.5, or 1.0 inches) on the establishment and yield of 'EG 1101' switchgrass. Planting between 0.25 and 0.5 inch generally resulted in more seedlings and greater stand percent and yield than 1.0‐inch depth. Tilling generally resulted in more initial seedlings at 30 days after planting (DAP) than no‐till with burning or mowing, but stand percent (150 DAP) and yield (postfrost) were not affected by seedbed preparation later in the growing season. However, all seedbed preparations and planting depths produced successful switchgrass stands of >1 seedling/ft 2 and ≥50% stands. Producers planting on land susceptible to erosion could consider no‐till planting after burning or mowing in order to reduce soil erosion and promote better soil structure and fertility without any loss in switchgrass productivity.